Trabalho pedagógico com leitura e escrita na pandemia: o que dizem as pesquisas acadêmicas? - Ferreira, Ana Paula (2025)
The present master's work is linked to the line of Training, Teacher Professionalization and Educational Work of the Graduate Program in Education of the Federal University of Goiás and to the Kadjót research group (Interinstitutional Group of Studies and Research on the Relations between Technologies and Education). Based on the historical-dialectical materialist method (MHD) as a theoretical-methodological foundation to understand the object studied (Kopnin, 1978; Kosik, 1995; Lefebvre, 1975) and based on Historical-Cultural Theory (Vigotski, 2007; 2009, 2017; Mendonça, 2018; Rigon; Asbahr; Moretti, 2010; Smolka, 2012), we understand reading and writing as the basis for other learning, being the gateway to all subsequent developmental processes. Since it is through education that the individual is humanized, formed, becomes aware of the environment in which he is part and transforms. The research in question presents the following research problem: how did academic research portray the pedagogical work with reading and writing in the pandemic period? In this context, through a state-ofknowledge research, we sought to explain the pedagogical work in academic research on reading and writing in the early years of elementary school during the pandemic. Academic works published in the Brazilian Digital Library of Theses and Dissertations (BDTD), with a time frame between the years 2020 and 2023, were analyzed, based on descriptors pertinent to the object. The corpus of the research was consolidated in six dissertations and two theses, only one of which was authored by men and without any research from graduate programs (PPG) in the north and south regions of the country. The PPGs from which the research originated are linked to the area of Education, Special Education, Knowledge and Social Inclusion, Digital Technologies and Language. The main themes addressed by the research were: pedagogical transposition from face-to-face to remote; reading and writing practices with digital technologies; students' meanings for their literacy and appropriation of writing. In all researches, the use of digital technologies was portrayed, including cell phones, computers, notebooks, tablets, and analog resources to carry out activities, such as printed materials, pencils and paper. Six of them pointed out that there were difficulties in teaching literacy in times of pandemic. However, it was possible to carry out reading and writing activities and, according to the research, the interaction between students, teachers and media was expanded. Finally, we understand that the pedagogical work for reading and writing in the pandemic period was portrayed in a way that met the expectations of remote emergency teaching (ERE), in which they contemplated the production of texts in digital supports, videos, music, podcasts, creation of an application to capture children's initial writing, teaching based on equivalence with stimuli in matrices for reading sentences, the use of platforms, websites, virtual learning environments (VLE), applications, social networks and web conference spaces, which allowed contact with students online and remotely. However, it was pointed out that not everyone was able to participate due to the absence of technological devices, so deliveries of printed materials to students were carried out. The way pedagogical work was developed during the pandemic triggered an excessive workload, in addition to those carried out in schools. There was a transposition of the activities carried out in the classroom to the screens, and the participation of the families to conduct the activities was relevant in the period, however, they did not always exist. Researchers and teachers sought to meet the guidelines for the area of education in the pandemic period, even with so many challenges. The theoretical strands that supported the process of appropriation of reading and writing in Brazil are constructivism and literacy, and constructivism, supported by current government policies, has guided the bias of learning to learn, and based teaching for the development of skills and abilities, meeting the demands of the market. Contrary to this conception, only one research approaches the historicalcultural perspective, as it understands that learning consists of the process of appropriation of cultural objects, which are the result of interaction, social/pedagogical mediation and language. Dealing with the appropriation of reading and writing from a socio-historical perspective is synonymous with becoming aware, through a process of complexification of the first verbal language, which is transformed into internal language and becomes more complex into written language, therefore, humanizing, transformative and basic for other learning